2018
DOI: 10.3389/fpsyg.2018.00343
|View full text |Cite
|
Sign up to set email alerts
|

The Bright, the Dark, and the Blue Face of Narcissism: The Spectrum of Narcissism in Its Relations to the Metatraits of Personality, Self-Esteem, and the Nomological Network of Shyness, Loneliness, and Empathy

Abstract: Grandiose and vulnerable narcissism seem to be uncorrelated in empirical studies, yet they share at least some theoretical similarities. In the current study, we examine the relation between grandiose (conceptualized as admiration and rivalry) and vulnerable narcissism in the context of the Big Five personality traits and metatraits, self-esteem, and their nomological network. To this end, participants (N = 314) filled in a set of self-report measures via an online survey. Rivalry was positively linked with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 137 publications
(118 citation statements)
references
References 75 publications
(154 reference statements)
4
113
0
1
Order By: Relevance
“…The results reported in the current study provide an opportunity to rethink the structure of narcissism on the basis of the theoretical foundations laid by the NSM (Krizan & Herlache, ) and elaborated on by the CPM (Strus & Cieciuch, ). Reports from previous research on grandiose narcissism (Kowalski, Vernon, & Schermer, ; Miller, Lynam, Hyatt, & Campbell, ; Rogoza, Żemojtel‐Piotrowska, et al, ) and vulnerable narcissism (Miller, Lynam, Vize, et al, ; Rogoza et al, ) have been generally supported by our results.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The results reported in the current study provide an opportunity to rethink the structure of narcissism on the basis of the theoretical foundations laid by the NSM (Krizan & Herlache, ) and elaborated on by the CPM (Strus & Cieciuch, ). Reports from previous research on grandiose narcissism (Kowalski, Vernon, & Schermer, ; Miller, Lynam, Hyatt, & Campbell, ; Rogoza, Żemojtel‐Piotrowska, et al, ) and vulnerable narcissism (Miller, Lynam, Vize, et al, ; Rogoza et al, ) have been generally supported by our results.…”
Section: Discussionsupporting
confidence: 90%
“…Vulnerable narcissism has been found to be located in greatest proximity to Gamma‐Minus/Disharmony, which is primarily defined by high neuroticism, just as expected (Strus & Cieciuch, ). Apart from neuroticism, of great interest is the nature of its other major component, which has been the subject of much debate: Miller, Lynam, Vize, et al () suggested a relationship with low agreeableness in contrast to Rogoza et al () who argued for low extraversion. The present results corroborate both of these claims as some entitlement rage has been found to represent social antagonism and was located near Alpha‐Minus/Disinhibition, while hiding the self represents apathy and submissiveness, and was located near Beta‐Minus/Passiveness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations